PELATIHAN KEBIJAKAN HUKUM PIDANA DALAM MELINDUNGI SATWA BAGI CALON JAKSA PADA BADAN DIKLAT KEJAKSAAN RI - Adhari, Ade; Naomi, Sherryl (Jurnal Serina Abdimas, 2023)
The existence of animals in Indonesia, especially endangered species, is decreasing in population due to rampant huntingactivities carried out by humans. Apart from going through the Criminal Code, the Government has made policies toregulate hunting activities and to protect animals from extinction. One of them is through the Republic of Indonesia Law.No. 5 of 1990 concerning Conservation of Living Natural Resources and Ecosystems. In addition, criminal law policiesare important to know in order to protect animals in Indonesia. This community service activity is to provide informationrelated to criminal law policies in protecting animals for prospective prosecutors at the Attorney General's TrainingAgency of the Republic of Indonesia. Participants in this activity are Prospective Prosecutors who are currentlyconducting training at the Prosecutor's Training Agency of the Republic of Indonesia. The aim of this PKM is to providean understanding of criminal law policies in animal protection. The method of implementing PKM this time is the lecturemethod and evaluation of the results of the lectures held at the Prosecutor's Office of the Republic of Indonesia. The resultsof the community service activities show that prospective prosecutors gain understanding regarding criminal law policiesin protecting animals, which will later be useful for prosecutors in carrying out their duties.   ABSTRAKKeberadaan satwa di Indonesia khususnya satwa langka semakin menipis populasinya karena maraknya kegiatanperburuan yang dilakukan oleh manusia. Selain melalui Kitab Undang-Undang Hukum Pidana, Pemerintah membuatkeijakan untuk menertibkan kegiatan perburuan dan untuk melindungi satwa dari kepunahan. Salahsatunya melalui UURI. No. 5 Tahun 1990 tentang Konservasi Sumber Daya Alam Hayati dan Ekosistem. Selain itu kebijakan hukum pidanamenjadi penting untuk diketahui guna perlindungan bagi satwa di Indonesia. Kegiatan pengabdian kepada masyarakat iniuntuk memberikan informasi berkaitan dengan kebijakan hukum pidana dalam melindungi satwa bagi calon jaksa padabadan diklat kejaksaan republik Indonesia. Peserta dalam kegiatan ini adalah Calon Jaksa yang sedang melakukanpelatihan di Badan Diklat Kejaksaan Republik Indonesia. Tujuan PKM ini adalah memberikan pemahaman kebijakanhukum pidana dalam perlindungan satwa. Metode pelaksanaan PKM kali ini adalah metode ceramah dan evaluasi atashasil ceramah yang dilaksanakan di Badan Diklat Kejaksaan Republik Indonesia. Hasil kegiatan pengabdian kepadamasyarakat menunjukan para calon jaksa mendapatkan pemahaman berkaitan dengan kebijakan hukum pidana dalammelindungi satwa, yang nantinya akan berguna bagi jaksa dalam menjalankan tugasnya.